AT1-receptor blockade, but not renin inhibition, reduces aneurysm growth and cardiac failure in fibulin-4 mice. Issue 4 (April 2016) - te Riet, Luuk; van Deel, Elza D.; van Thiel, Bibi S.; Moltzer, Els; van Vliet, Nicole; Ridwan, Yanto; van Veghel, Richard; van Heijningen, Paula M.; Robertus, Jan Lukas; Garrelds, Ingrid M.; Vermeij, Marcel; van der Pluijm, Ingrid; et al.
Abstract : Aims: Increasing evidence supports a role for the angiotensin II-AT1 -receptor axis in aneurysm development. Here, we studied whether counteracting this axis via stimulation of AT2 receptors is beneficial. Such stimulation occurs naturally during AT1 -receptor blockade with losartan, but not during renin inhibition with aliskiren. Methods and results: Aneurysmal homozygous fibulin-4 R/R mice, displaying a four-fold reduced fibulin-4 expression, were treated with placebo, losartan, aliskiren, or the β-blocker propranolol from day 35 to 100. Their phenotype includes cystic media degeneration, aortic regurgitation, left ventricular dilation, reduced ejection fraction, and fractional shortening. Although losartan and aliskiren reduced hemodynamic stress and increased renin similarly, only losartan increased survival. Propranolol had no effect. No drug rescued elastic fiber fragmentation in established aneurysms, although losartan did reduce aneurysm size. Losartan also increased ejection fraction, decreased LV diameter, and reduced cardiac pSmad2 signaling. None of these effects were seen with aliskiren or propranolol. Longitudinal micro-CT measurements, a novel method in which each mouse serves as its own control, revealed that losartan reduced LV growth more than aneurysm growth, presumably because the heart profits both from the local (cardiac) effects of losartan and its effects on aortic root remodeling. Conclusion: Losartan, but not aliskiren or propranolol, improved survival in fibulin-4 R/R mice. This most likely relates to its capacity to improve structure and function of both aorta and heart. The absence of this effect during aliskiren treatment, despite a similar degree of blood pressure reduction and renin–angiotensin system blockade, suggests that it might be because of AT2 -receptor stimulation.